Implikasi Hukum Restrukturisasi Kelembagaandan Pembentukan Kementerian Baru dalam KerangkaTata Kelola Pemerintahan Indonesia - Tungga, Benyamin; Jamil, Jamil; Sukadi, Imam (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the policy of establishing new ministries, the legal implications of institutional restructuring, and its impact on the effectiveness of governance within the framework of Indonesian constitutional law. The background to this research is the formation of new ministries during Prabowo's administration, which sparked debate about the effectiveness of governance and legal certainty. The urgency lies in the potential for institutional restructuring to cause regulatory inconsistencies, overlapping authorities, and administrative legitimacy uncertainties if not supported by a comprehensive legal framework. The research uses a normative juridical method with a legislative, conceptual, and comparative approach through qualitative analysis of legal materials. The results show that restructuring can improve government effectiveness through functional specialization and increased accountability, but also risks creating coordination complexity and legal uncertainty without adequate regulatory harmonization and oversight. Therefore, the formation of ministries must be placed within the framework of the principle of legality and limitation of power. The novelty of this research lies in the model of institutional restructuring analysis that integrates institutional design, legal certainty, and constitutional oversight as prerequisites for sustainable government effectiveness.  Penelitian ini bertujuan menganalisis kebijakan pembentukan kementerian baru, implikasi hukum restrukturisasi kelembagaan, serta dampaknya terhadap efektivitas pemerintahan dalam kerangka hukum tata negara Indonesia. Latar belakang penelitian ini adalah pembentukan kementerian baru pada era pemerintahan Prabowo yang memicu perdebatan mengenai efektivitas tata kelola dan kepastian hukum. Urgensinya terletak pada potensi restrukturisasi kelembagaan yang menimbulkan ketidaksinkronan regulasi, tumpang tindih kewenangan, dan ketidakjelasan legitimasi administratif apabila tidak didukung kerangka hukum yang komprehensif. Penelitian menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif melalui analisis kualitatif bahan hukum. Hasil penelitian menunjukkan bahwa restrukturisasi dapat meningkatkan efektivitas pemerintahan melalui spesialisasi fungsi dan peningkatan akuntabilitas, namun juga berisiko menimbulkan kompleksitas koordinasi dan ketidakpastian hukum tanpa harmonisasi regulasi dan pengawasan memadai. Oleh karena itu, pembentukan kementerian harus ditempatkan dalam kerangka asas legalitas dan pembatasan kekuasaan. Kebaruan penelitian ini terletak pada model analisis restrukturisasi kelembagaan yang mengintegrasikan desain institusional, kepastian hukum, dan pengawasan konstitusional sebagai prasyarat efektivitas pemerintahan berkelanjutan.
Keywords: Efektivitas Pemerintahan; Kementerian Baru; Restrukturisasi Kelembagaan